2022
DOI: 10.3390/plants11131675
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Review of Mexican Plants with Teratogenic Effects

Abstract: In Mexico, the use of medicinal plants is the first alternative to treat the diseases of the most economically vulnerable population. Therefore, this review offers a list of Mexican plants (native and introduced) with teratogenic effects and describes their main alterations, teratogenic compounds, and the models and doses used. Our results identified 63 species with teratogenic effects (19 native) and the main alterations that were found in the nervous system and axial skeleton, induced by compounds such as al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…Pregnancy is a condition that should be considered a time of minimal medical intervention, even in the consumption of plant-based products. This is because it has been described that a wide variety of congenital deformities usually occur in the fetus during the period of organogenesis [ 44 ]. Mainly, it is because xenobiotic-metabolizing enzymes are induced during pregnancy, which can increase the metabolism of secondary metabolites that are substrates of these enzymes, causing intoxication by them [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is a condition that should be considered a time of minimal medical intervention, even in the consumption of plant-based products. This is because it has been described that a wide variety of congenital deformities usually occur in the fetus during the period of organogenesis [ 44 ]. Mainly, it is because xenobiotic-metabolizing enzymes are induced during pregnancy, which can increase the metabolism of secondary metabolites that are substrates of these enzymes, causing intoxication by them [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of consuming some metabolites such as alkaloids during pregnancy must be evaluated since exposure to these compounds may cause defects in developing embryos and fetuses. [12][13][14][15][16] In fact, in a previous study, we showed that orogastric consumption of B. frutescens L. at concentrations equivalent to those used for human consumption 11 during the organogenesis period produces teratogenic effects, including external (umbilical hernia and growth retardation) and internal alterations (central rib ossification). 17 In addition, during gestation, external factors such as inadequate maternal diet and exposure to pollutants and toxins significantly affect the development of the fetal nervous system and may therefore increase the risk of neurodevelopmental/psychiatric disorders.…”
Section: Introductionmentioning
confidence: 96%
“…The occurrence of DNA damage has the potential to interfere with typical cellular processes such as division, replication, and gene expression, which may result in the emergence of genetic mutations and developmental anomalies. [22] Taking all of this into mind, the purpose of the current study is to carry out an in-depth investigation into the teratogenic effects that the aqueous extract of Bambusa vulgaris (AEBV) has on Wistar albino rats. The existence of multiple organ malformations, including morphological, structural, and skeletal abnormalities, suggests that the embryonic growth may be affected by a variety of pathways due to the presence of toxic chemicals in AEBV.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of DNA damage has the potential to interfere with typical cellular processes such as division, replication, and gene expression, which may result in the emergence of genetic mutations and developmental anomalies. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%